Using your GoPro Hero3+ - Rich, Jason (Que, 2014)
"Using Your GoPro Hero3+: Learn to Shoot Better Photos and Videos (Que Video) is a two hour instructional video that introduces viewers to the power, capabilities and versatility of the GoPro Hero3+ camera. Photographer and author, Jason R. Rich, explains exactly how to set up and use the GoPro Hero3+, offers easy-to-implement photography strategies for shooting in a wide range of situations, plus explains how to transfer, edit, enhance and share images and videos shot using the camera. This video also offers tips for selecting, and then using, many of the most popular mounts and accessories available for the GoPro Hero3+ camera. As explained within this video, mounts and accessories help the user overcome various obstacles when shooting in low-light, underwater, or in otherwise less than optimal shooting conditions."--Resource description page.